Exploring the constructivist mentoring program in developing EFL teacher professionalism: A qualitative approach - Nugroho, Kurniawan Yudhi; Sakhiyya, Zulfa; Saleh, Mursid; Mujiyanto, Januarius; Rukmini, Dwi (Universitas Pendidikan Indonesia, 2020)
This paper investigates the implementation of constructivist learning, as it was practiced by five EFL teachers at a vocational high school in Indonesia. We offer a ‘mentoring program’ for teachers to support each other and provide resources that are bottom-up, free, and relevant, conducted in a collegial atmosphere. We adopted a qualitative approach as it enabled us to understand and cultivate deeper the learning process that occurred in the classroom. Data were qualitatively collected and analyzed in two ways. First, it focused on the participants’ interview, observation, self-reflection and discussion on the variables in the mentoring program covering the need and expectation of EFL teachers in the formal pedagogical setting, sources of teachers’ resistance to participate in Teacher Professional Development (TPD) program, the impact of TPD program on the teacher pedagogical competence, and conditions contributing to sustainable development as a result in the TPD program. Second, it was to disclose the researchers’ viewpoints and reflections under variables, as stated in the earlier analysis. Our research findings suggested that constructivist-learning practices were proven to be successful in helping the teachers experienced promising mentoring progress of TPD. Teachers and students underwent a significant change as the learning activities became more engaging and fun. Teachers confessed to have their pedagogical knowledge and practice expanded while having their attitude and mindset shifted after going through a series of activities inside the mentoring program. The program was central in nurturing teachers’ self-identity and helping them overcome their internal blocks. In the longer-term, this program contributes to developing teacher professionalism as they started to see the potentials and positives impacts of TPD programs.